Functional Syllabus with Eco-Theological Focus: Language Use for Environmental Advocacy within Islamic Contexts - Kalayo Hasibuan; Hidayah Azzulfah; Melda Fitriyani; Najwa Aura Rullianda (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This paper proposes a functional syllabus with an eco-theological focus to integrate language learning with environmental advocacy in Islamic contexts. Grounded in Islamic principles such as khalīfah (stewardship) and amānah (trust), the study aims to show how communicative language functions like expressing concern, persuading, and proposing solutions can foster both linguistic competence and ecological awareness. The paper outlines theoretical foundations and practical applications of embedding Islamic environmental ethics into language teaching, suggesting that this approach promotes meaningful, value-based communication and strengthens learners’ moral responsibility toward the environment